2018
DOI: 10.1177/1071100718800836
|View full text |Cite
|
Sign up to set email alerts
|

Combined Intramedullary Nail Coated With Antibiotic-Containing Cement and Ring Fixation for Limb Salvage in the Severely Deformed, Infected, Neuroarthropathic Ankle

Abstract: Limb preservation for the severely deformed, infected, and unstable Charcot neuroarthropathic ankle is challenging. Nonoperative management may not adequately control evolving deformities, leading to nonhealing ulcerations, osteomyelitis, and amputation. Ninety percent of foot and ankle Charcot neuroarthropathy operations involve the ankle joint, 36 yet only 10% of Charcot cases occur at the ankle/ subtalar joint, 35 suggesting the difficulties with nonoperative treatment. Operative reconstruction for the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Tomczak et al. 2019 [ 27 ] Case series 8 patients Hindfoot intramedullary nail (Tri-gen Hindfoot 10 mm × 160 mm, Smith and Nephew, Memphis, TN) with simultaneous use of external fixation Clinically osteomyelitic deformed neuropathic ankles PMMA (Simplex P with tobramycin, Stryker, Mahwah, NJ) 1 g vancomycin additionally Circumferentially Not reported Sterile silicone tube 88% (7/8) 88% (7/8) 41. Dar et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tomczak et al. 2019 [ 27 ] Case series 8 patients Hindfoot intramedullary nail (Tri-gen Hindfoot 10 mm × 160 mm, Smith and Nephew, Memphis, TN) with simultaneous use of external fixation Clinically osteomyelitic deformed neuropathic ankles PMMA (Simplex P with tobramycin, Stryker, Mahwah, NJ) 1 g vancomycin additionally Circumferentially Not reported Sterile silicone tube 88% (7/8) 88% (7/8) 41. Dar et al.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, clinically beneficial constructs were also created with use of knee and ankle arthrodesis implants [ 19 , 26 ], and some authors even reported coating of inverse shoulder prosthesis and plates used for revisions of septic loosening and for fracture fixation [ 8 ], respectively. To provide more protection across the fusion site and aid in early weight-bearing, some authors reported using antibiotic-containing coated IM nails in combination with simultaneous external ring fixation in cases of unstable infected neuropathic ankles in obese patients [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The techniques may be regarded as salvage procedures in neglected adult clubfoot, challenging ulcerations, ankle joint arthrodesis for treating Charcot neuroarthropathy despite the complications[ 96 , 100 - 103 ]. Thus, a hybrid technique of circular EF and an intramedullary nail coated with antibiotic cement salvaged lower limbs in most patients and achieved a functional and clinically stable foot in infected neuropathic ankles[ 104 ]. Infected ankles were also salvaged with the Ilizarov method[ 104 - 106 ].…”
Section: Current Clinical Practice and Research In The Ilizarov Techniques Of Bone Reconstructionmentioning
confidence: 99%
“…Thus, a hybrid technique of circular EF and an intramedullary nail coated with antibiotic cement salvaged lower limbs in most patients and achieved a functional and clinically stable foot in infected neuropathic ankles[ 104 ]. Infected ankles were also salvaged with the Ilizarov method[ 104 - 106 ]. Reconstruction of the hind foot and ankle with concurrent lengthening through a distal tibial corticotomy utilizing the Ilizarov frame was found comparable to other treatment alternatives[ 107 ].…”
Section: Current Clinical Practice and Research In The Ilizarov Techniques Of Bone Reconstructionmentioning
confidence: 99%